2018
DOI: 10.1111/aas.13130
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and necrotizing soft tissue infections—A prospective observational cohort study: Statistical analysis plan

Abstract: The study will provide important data on patients with NSTI and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…People with diabetes have more severe and frequent bacterial infections and a higher mortality rate than people without diabetes. Studies have shown that skin and soft tissue infection was more common in patients with diabetes, followed by urinary infections 35 . Co‐infection was much more common in patients with diabetes, and the infection involved more sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with diabetes have more severe and frequent bacterial infections and a higher mortality rate than people without diabetes. Studies have shown that skin and soft tissue infection was more common in patients with diabetes, followed by urinary infections 35 . Co‐infection was much more common in patients with diabetes, and the infection involved more sites.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that skin and soft tissue infection was more common in patients with diabetes, followed by urinary infections. 35 Co-infection was much more common in patients with diabetes, and the infection involved more sites. Consequently, the rate of admission due to infection was also higher.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of NSTI was made by the surgeon during the primary operation. It is based on, but not restricted to, findings of necrosis, dissolved or deliquescent soft tissue, and fascial and muscular affection (22). The invasive non-NSTI SA control strains consisted in Bloodstream infection (BSI) strains (12 infective endocarditis, 9 bacteremia without infective endocarditis) collected during a prospective cohort study on S. aureus bacteremia (VIRSTA) (23).…”
Section: Methodsmentioning
confidence: 99%